Hexadecanuclear Copper Monothiocarbonates: An Emissive Cluster Building Block. Issue 13 (5th April 2017) - Gupta, Arvind K.; Kishore, Pilli V. V. N.; Liao, Jian‐Hong; Chen, Yuan‐Jang; Liu, C. W.
Abstract : A novel Cu I cluster, Cu16 L16 · 2CH3 COCH3 (1 ), derived from a cyclohexylmonothiocarbonate ligand (L) was synthesized and structurally characterized. Coordinated‐solvent‐replacement reactions of1 with various N‐donor ligands to provide2 –5 were demonstrated. Clusters1 –3 and5 display photoluminescence, whereas4 is nonemissive. It appears that the emission characteristic of1 can be tuned by ancillary N‐donor ligands. Abstract : The high‐yielding synthesis of the first luminescent polynuclear Cu I cluster stabilized by monothiocarbonate ligands is illustrated. Tuning of the photoluminescence properties with various N‐donor ligands is demonstrated.